Assessing Financial Reporting Quality of Company Limited by Guarantee Charities in Malaysia Using Benford’s Law: A Preliminary Study - Sharon, Cheuk; Esmie, Nichol; Tin Hla, Daw; Michael, Tinggi (Human Resource Management Academic Research Society, 2021)
The issue of terrorism is experienced at the global level, and it has been recognised that such activities need financing from various sources, legitimate and illegitimate. A legitimate source is via non-profit organisations. It has been advocated that effective investigation and information gathering be done at the country-level to facilitate the detection of terrorist abuse of non-profit organisations; such information would include financial information. In view of the foregoing, a comprehensive assessment of the financial reporting quality of non-profit organisations would be a useful step in conducting an overall risk analysis of the non-profit sector. The objective of this study is to assess the financial reporting quality of charities in Malaysia. The financial statements of 235 companies limited by guarantee were extracted for the years 2016, 2017 and 2018 resulting in 7,056 observations. Digital analysis was performed to review the conformity of first and second digit distributions with that of Benford’s Law; the main statistics of the log mantissa and the Mean Absolute Deviation were also computed. Subsequently, statistical tests were run to evaluate data conformity to Benford’s Law. Findings were found to be mixed and inconclusive. Implications of the study’s findings and suggestions for further research were further discussed.